CHRONIC PAIN AND DEPRESSION - ARBITRARINESS OR CONSECUTION OF THE PATIENT'S DIAGNOSTIC AND TREATMENT ROUTE - Tatyana Telbizova; Ivan Aleksandrov; Mariana Arnaoudova (Peytchinski Publishing, 2021)
Unrecognized depression among patients with chronic pain is a common medical problem, highlighting the need for targeted search and identification of depression-related symptoms. Purpose: The aim of the present study is to investigate the trends in the diagnostic and treatment pathway of comorbid patients with depression and chronic pain. Materials and Methods: 110 psychiatrists and 119 neurologists were interviewed through an anonymous, randomized survey in Bulgaria. Results: Referrals of the patients with chronic pain to neurologists and psychiatrists are not routine practice. The general practitioners are the main group, referring the patients with chronic pain to a consultation with a neurologist (89.10%) and a psychiatrist (68.20%). The patients themselves seek help more often from a neurologist (77.20%) than from a psychiatrist (44.50%). The most common reason for neurologists to consult their patients with a psychiatrist issuicidal ideation and intentions (50.42%) and the least common -insomnia (15.96%). According to psychiatrists, chronic pain patients seek help from them for other symptoms like somatic - vegetative ones (97.8%), anxiety (78.20%), insomnia (55.50%) and depressed mood (54.50%). More than 1/4 (29%) of them have had suicidal thoughts and intentions, which suggests a long history of depressive symptoms. Conclusions: The diagnostic and treatment processes of patients with chronic pain and depression are performed randomly rather than following a certain logical sequence. The creation of an algorithm for general practitioners and pain specialists aimed at early detection of symptoms of depression and related predictors of suicidal behavior is needed.